INDUCED ABORTION IN THE LITERATUREFROM 2020 TO 2024 - Gonzalez, Mariia del Rosario Molina (IPHO-Journal of Advance Research in Science And Engineering, 2024)
Pregnancy interruption policies are distinguished by orienting opinions, decisions,and behaviors towards the individual request for abortion, even when the literature indicates that the choice of partner is defined by the group closest to the person, the strategies ofthegovernment seem to focus on the personal motives of those requesting the service. The objective of this work was to establish the sociopolitical and socio-cognitive dimensions of abortion. A documentary, exploratory,and psychometric work was carried out with a sample of 100 students from a public university selected for their internships and professional service in public health institutions. The results show a reductionofthree factorsoutof the six reported in the literature. The reduction to three factors and eleven indicators is recommendedtoadjust the instrument to the sample and its scenario of expectations of termination of pregnancy.